Advanced fine line double printing process for manufacturing high efficiency silicon wafer solar cells. (1st March 2019) - Shetty, Kishan; Kaushal, Yudhbir; Murthy, D.S.; Kumar, Chandra Mauli
Highlights: Double printing process using advanced screen & paste is demonstrated. Practical difficulties with double printing process are discussed. A significant improvement in Isc and FF was achieved using double printing process. The process flow, results, QE and Ag paste laydown results are discussed. A gain in cell efficiency was achieved at no additional cost. Abstract: A double print technology using a front contact screen pattern of high precision ultra-fine line finger openings is demonstrated in this work. It has helped in achieving an absolute cell efficiency gain of over 0.25% compared to conventional single printing process. A suitable silver paste was applied to both single and double printing process resulting in improved results and a lower paste laydown for double printing process. This paper represents the work done after the double print process from trial phase reached a matured level with the correct selection of screen design and paste compatibility to work well with the selected screens. A significant improvement in short circuit current (Isc) of almost 90 mA was realized for double printed cells due to increased print aspect ratio and active area for light absorption.